A mechanical tension-resistant device for lead rubber bearings. (1st December 2017) - Hu, Kai; Zhou, Ying; Jiang, Li; Chen, Peng; Qu, Ge
Highlights: Tension force in isolator is the main obstacle in expanding isolation technology in high-rise building. A novel tension-resistant device for rubber bearing is proposed. Working performance of the device under static load was analyzed numerically and experimentally. Shaking table test was conducted to verify its working performance under dynamic load. The effectiveness and applicability of the device is evaluated. Abstract: Tensile stresses in laminated rubber bearings can create expandable cavities and cause damage to spread inside the rubber, which may lead to inestimable impact on the mechanical performance of the isolators. Thus, laminated rubber isolation systems are mainly used in multistoried buildings in which compression state is maintained at the bottom of the structure, such as the low-rise buildings. The systems are not as commonly adopted in high-rise construction and buildings with large aspect ratio, due to large overturning moments and subsequent development of tensile forces at the base. A new type of tension restraining device to be used in conjunction with LRBs is proposed which can keep the tensile stress in the rubber under the limit value, while adapting to horizontal deformation of the rubber bearing by interaction and sliding between the components of the device. Numerical analysis and low-cycle load test of the prototype isolators with the tension restraint device were carried out to study the performance of the device in limited tensile condition, shear-compression condition and shear-tension condition. Additionally, a shake table test of a 1:15 scale high-rise frame-core tube isolated structure is presented to investigate the performance of the proposed device under dynamic actions. Results indicate that the tension-restraint device can help protect the rubber from large tensile stresses and improve the tensile resistance of the isolator, while having little influence on the horizontal shear behavior of the bearings and their effect on the global behavior of the structure. The tension-restraint devices are promising systems to be used in tall buildings and those with large aspect ratios.